A Maqashid Shariah Review of the Fish Feed Debt Practice at CV Surya Pelangi, East Lampung - Rohmad Hidayatulloh; Finny Ligery; Ahmad Mukhlishin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the practice of fish feed debt transactions carried out by CV Surya Pelangi in East Lampung from the perspective of Maqashid Sharia. The debt system implemented by the company allows farmers to obtain feed on credit and make payments after harvest; however, the harvest must be sold back to the company at a price determined unilaterally. This condition is presumed to create an imbalance in economic relations and weaken the farmers’ bargaining position. This research uses a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation, then analyzed descriptively through data reduction, data presentation, and conclusion drawing. The results of this study indicate that the practice of fish feed debt transactions at CV Surya Pelangi is carried out in a simple, flexible, and trust-based manner, without interest or collateral, using oral agreements supported by transparent administrative records. From the perspective of maqashid shari’ah, this practice reflects the principles of hifzh al-din, hifzh al-nafs, hifzh al-‘aql, hifzh al-nasl, and hifzh al-mal through fairness, transparency, and protection from usury and exploitation, although there are still weaknesses in the formal contract aspect and potential psychological pressure. The impacts are multidimensional, including improving access to capital and business sustainability, as well as strengthening social relationships, but also potentially creating economic vulnerability, thus requiring further refinement to optimize farmers’ welfare. This study concludes that the practice of fish feed debt at CV Surya Pelangi is conducted in a simple, flexible, and trust-based manner, with oral agreements and transparent record-keeping, without interest, penalties, or collateral. In general, this practice is in line with maqashid shari’ah principles as it is free from riba, gharar, and fraud, and has a positive impact on business sustainability and farmers’ social relationships. However, improvements are still needed, particularly in formalizing contracts to enhance legal certainty